Molecular targeted therapy-related life-threatening toxicity in patients with malignancies. A systematic review of published cases - Assoun, Sandra; Lemiale, Virginie; Azoulay, Elie (Intensive care medicine, 2019)
Background Molecular targeted therapy increased overall and disease-free survival in a wide range of malignancies. Although generally well tolerated compared to chemotherapy, molecular targeted therapy may be associated with adverse events requiring ICU admission. Informing clinicians about clinical features of these toxic events might maintain awareness and favor early recognition, prompt diagnosis and treatment. Methods We performed a systematic review of published case reports of molecular targeted therapy-related life-threatening toxicity that led to ICU admission. The search used the Pubmed database using medical subject heading (Mesh) terms, including all FDA-approved molecular targeted therapy (TT), up to March 2019. No language restriction was applied. All cases reports of patients admitted to the ICU for molecular targeted therapy-related toxicity were included. Non-FDA-approved combinations of treatments or hormonal therapy were not included. Results Two hundred and fifty-three cases were identified. Nearly half of them ( n = 102; 40.3%) were related to anti-angiogenic agents, mostly for gastrointestinal and cardiovascular complications. Other molecules responsible for adverse events were chiefly immune checkpoint inhibitors ( n = 85, 33.6%), EGFR inhibitors ( n = 33; 13.0%), and anti-HER2 ( n = 10; 4.0%). They were associated with adverse events such as respiratory or hypersensitivity events. Management and outcomes associated with these life-threatening complications are reported. Conclusions Based on the vast number of treated patients, only 253 cases of molecular therapy-related severe toxicity are reported in cancer patients. Symptoms and biomarkers that depict these events need to be better identified as to allow appropriate reporting and improving dose and schedule of the treatment adapted to each patient.